2003
DOI: 10.1126/science.1089681
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Psychotomimetics Act Through a Common Signaling Pathway

Abstract: Three distinct classes of drugs: dopaminergic agonists (such as D-amphetamine), serotonergic agonists (such as LSD), and glutamatergic antagonists (such as PCP) all induce psychotomimetic states in experimental animals that closely resemble schizophrenia symptoms in humans. Here we implicate a common signaling pathway in mediating these effects. In this pathway, dopamine- and an adenosine 3',5'-monophosphate (cAMP)-regulated phospho-protein of 32 kilodaltons (DARPP-32) is phosphorylated or dephosphorylated at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
226
5
8

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 296 publications
(258 citation statements)
references
References 20 publications
19
226
5
8
Order By: Relevance
“…Given the large number of manipulations that are capable of altering sensorimotor gating (cf., Geyer et al, 2001Geyer et al, , 2002Swerdlow et al, 2001a), it is clear that the molecular and neural circuits regulating this automatic neural process are quite complex. Our work, and those of others measuring region-specific effects (eg Svenningsson et al, 2003), suggests another layer of complexity in the regulation of sensorimotor gating in that each brain region may have a unique molecular signature.…”
Section: Discussionsupporting
confidence: 55%
“…Given the large number of manipulations that are capable of altering sensorimotor gating (cf., Geyer et al, 2001Geyer et al, , 2002Swerdlow et al, 2001a), it is clear that the molecular and neural circuits regulating this automatic neural process are quite complex. Our work, and those of others measuring region-specific effects (eg Svenningsson et al, 2003), suggests another layer of complexity in the regulation of sensorimotor gating in that each brain region may have a unique molecular signature.…”
Section: Discussionsupporting
confidence: 55%
“…DARPP-32 + / + Â DARPP-32 + / + and DARPP-32 -/-Â DARPP-32 -/-mating was performed separately for no more than two generations. Mice bearing a mutation in which Thr34 or Thr75 were replaced by a nonphosphorylatable Ala (T34A and T75A mutant mice, respectively) (Svenningsson et al, 2003) were obtained from heterozygous animals generated from C57BL/6 Â 129SV hybrids bred for one generation on a C57BL/6 background. Mice were age matched, and both female and male offspring were used.…”
Section: Animalsmentioning
confidence: 99%
“…Indeed, several reports have shown that GSK-3b levels or its phosphorylation state (Ser-9-GSK3b), are altered among schizophrenic individuals (Kozlovsky et al, 2000(Kozlovsky et al, , 2001Beasley et al, 2001;Emamian et al, 2004). Moreover, GSK-3b has been shown to be a target of the action mood-stabilizers such as lithium and VPA ( Klein and Melton, 1996;Chen et al, 1999;Hall et al, 2002), antipsychotics drugs, as clozapine, haloperidol and risperidone (Alimohamad et al, 2005a, b) and psychotomimetics drugs, which induce an schizophreniclike state in humans and animal models (Svenningsson et al, 2003;Ahn et al, 2005).…”
Section: Schizophrenia and Polymorphisms In Frizzled 3 And Gsk3bmentioning
confidence: 99%